lncRNA FR215775 Regulates Th2 Differentiation in Murine Allergic Rhinitis - Yue Ma; Le Shi; Keqing Zhao; Chunquan Zheng (Journal of Immunology Research)
To identify the effect of long noncoding RNA (lncRNA) FR215775 in regulating CD4+ T cells on murine models of allergic rhinitis (AR), the expression of lncRNA FR215775 in primary Th2 cells was detected through qRT-PCR. After knocking down the expression of lncRNA FR215775 via Sh-FR215775-Ads, Cell Counting Kit-8, cytometric bead array, and fluorescence-activated cell sorting were performed to determine its functions in vitro. Moreover, lncRNA FR215775-silencing or nonsilencing cells were injected intravenously into AR mice. Then, hematoxylin and eosin, Alcian blue-periodic acid Schiff, and toluidine blue staining were performed, and the levels of IL-2, IL-4, IL-5, IL-6, IL-10, IL-17A, IFN-γ, and TNF in the AR mice were also determined. We found that the expression of lncRNA FR215775 was specifically higher in the murine primary Th2 cells. After the knockdown of lncRNA FR215775, the proliferation of CD4+ T cells was inhibited, and the expressions of IL-4 and IL-5 in the cell culture supernatant were significantly decreased (P<0.001), along with the percentage of Th2 cells (P<0.05). The lncRNA FR215775-silencing AR group showed less serious allergic symptoms and a low level of ovalbumin-specific immunoglobulin E (P<0.01). Meanwhile, the eosinophilia inflammation, goblet cell hyperplasia, and mast cell inflammation in the nasal mucosa all decreased, which indicated attenuated allergic inflammation in the lncRNA FR215775-silencing AR group. In addition, the Th2-related cytokines IL-4 and IL-5 were downregulated in the serum and nasal lavage fluid of this group (P<0.01). In conclusion, lncRNA FR215775 may play a vital role in the function and differentiation of Th2 cells, which may encourage allergic inflammation. These results may provide significant insights into AR pathogenesis and offer new treatment targets for alleviating AR.